Co-design and Sustainable Food in Vietnam - Jotte de Koning (TU Delft OPEN Publishing, 2023)
This "Co-design of Sustainable Food in Vietnam" booklet is written for everyone, especially companies, consumers and experts, who want to organize a co-design workshop in Vietnam, with focus on food and sustainability. It includes the methodology, a step-by-step facilitation manual and the results of implemented co-design workshops. We hope that readers will be equipped with enough knowledge and be inspired to conduct more and more co-creation activities. The booklet was published in 2019 by the Asian Institute of Technology in Taiwan.
Keywords: 300; sustainable Food; co-design; sustainable products; food consumption; co-design for sustainable food; food in Vietnam